Yusifbayli, Nurali - (:unkn) unknown (My University, 2026)
He was born on March 28, 1963, in the Republic of Azerbaijan. He is of Azerbaijani nationality. In 1980, he was admitted to the full-time department of the Faculty of Electric Power Engineering at the Kyiv Polytechnic Institute (currently Kyiv Technical Academy), and graduated in 1986 with a degree in Cybernetics of Electrical Systems. From 1986 to 1989, he worked at Sumgait Thermal Power Plant No. 1 as an electrician, shift supervisor of the electrical workshop, and shift supervisor of the power plant. Between 1989 and 1993, he held the positions of Dispatcher and Senior Dispatcher at the state company “Azerenergy.” From 1993 to 2001, he served as Head of the Central Dispatch Service, Chief Dispatcher, and Deputy Chief Engineer of “Azerenergy” OJSC. In 2001–2002, he worked as Deputy General Director of the “Energy Transmission” Production Union of “Azerenergy” OJSC. Between 2002 and 2009, he was Head of the Central Dispatch Department, and from 2009 to 2012, Director of the “Azerbaijan Scientific-Research and Design Institute of Power Engineering” under “Azerenergy” OJSC. During this period, he also served as Chairman of the Specialized Dissertation Council in the specialty 05.14.02 – Power Stations and Electric Power Systems under the Higher Attestation Commission of the President of the Republic of Azerbaijan. Since 2012, he has worked as Chief Advisor and Advisor to the Minister at the Ministry of Economy and Industry of the Republic of Azerbaijan. From 2014, he served as Head of the Strategic Planning Department of the same ministry. By the Order No. 11101 of the President of the Republic of Azerbaijan dated March 13, 2015, he was appointed Deputy Chairman of the State Agency on Alternative and Renewable Energy Sources. By Presidential Order No. 1159 dated September 22, 2020, he was relieved of this position. By Order No. K-44 of the Minister of Education of the Republic of Azerbaijan, he was appointed Vice-Rector for Academic Affairs of Azerbaijan Technical University on January 18, 2021. By the Order of the President of the CIS Electric Power Council dated October 20, 2004, he was awarded the honorary title “Honored Power Engineer of the CIS.” By the Order of the President of the Republic of Azerbaijan dated October 19, 2005, he was awarded the honorary title “Honored Engineer of the Republic of Azerbaijan.” In 2011, he was awarded the “Golden Buta” prize for his contributions to improving the application of scientific and design solutions in the functioning and development of Azerbaijan’s electric power system. By the Presidential Order dated October 21, 2014, he was awarded the honorary title “Honored Scientist of the Republic of Azerbaijan.” He was awarded second place in the Innovation Competition jointly organized by the Ministry of Economy of the Republic of Azerbaijan and the United Nations Representation in Azerbaijan, and first place according to the evaluation of FAO. From 1990 to 1994, he completed postgraduate studies at the Azerbaijan Scientific-Research Institute of Power Engineering. In 1997, he defended his PhD dissertation on “Regulation of Placement Parameters of TAT Devices in Complex Electric Power Systems,” and in 2004, he defended his doctoral dissertation on “Theoretical and Methodological Foundations of Dispatch Management under New Conditions.” He holds a Doctor of Technical Sciences degree and the title of Professor. He is the author of 8 books, 4 author’s certificates, 1 textbook, 3 patents, 3 Azerbaijan standards, and more than 170 scientific publications. He is the Editor-in-Chief of the international scientific-industrial journal “ELECTRO-energetics-technics-mechanics+control.” He is the Chairman of the Dissertation Council registered under number ED 2.04 at the Higher Attestation Commission under the President of the Republic of Azerbaijan. He is a member of the international Institute of Electrical and Electronics Engineers (IEEE), editorial boards of the journals “Problems of Energy” and “Applied Mathematics,” as well as scientific councils of several research institutes. Since 1998, he has been engaged in teaching activities and currently works as a Professor at the Department of Management and Automation at Azerbaijan Technical University.